10-Year Survival Rates After High Tibial Osteotomy Using Angular Stable Internal Plate Fixation: Case Series With Subgroup Analysis of Outcomes After Combined Autologous Chondrocyte Implantation and High Tibial Osteotomy. Issue 2 (23rd February 2022) - Bode, Lisa; Eberbach, Helge; Brenner, Anna-Sophie; Kloos, Ferdinand; Niemeyer, Philipp; Schmal, Hagen; Suedkamp, Norbert P.; Bode, Gerrit
Background: Good-to-excellent midterm results after high tibial osteotomy (HTO) to treat medial compartment cartilage defects or osteoarthritis (OA) have been published, but little is known about long-term survival rates in terms of conversion to total knee arthroplasty (TKA) using angular stable internal plate fixation. Purpose: To determine TKA-free survival rates and functional and radiological outcomes at 10 years after HTO. A subgroup analysis of patients who underwent combined HTO and autologous cartilage implantation (ACI) was also performed. Study Design: Case series; Level of evidence, 4. Methods: Included were 125 patients with a mean follow-up of 9.90 ± 2.25 years; 90 patients underwent HTO for medial OA, and 35 patients underwent ACI and HTO for medial focal cartilage defects. Functional outcome measures included visual analog scale (VAS) for pain, Lysholm, International Knee Documentation Committee (IKDC), and Knee injury and Osteoarthritis Outcome Score (KOOS) subscales and KOOS4 (average of 4 KOOS subscales: Pain, Symptoms, Sport, and Quality of Life). Radiological outcomes included lateral distal femoral angle, medial proximal tibial angle, and joint line convergence angle. Results: Overall, 16 patients required conversion to TKA at a mean 86.75 ± 25.73 months (10-year survival rate, 87.2%). Only 2 patients in the HTO+ACI subgroup required a conversion to TKA (10-year survival rate, 94.3%). The complication rate for all patients was 8.8%. In both the HTO and HTO+ACI subgroups, VAS pain levels decreased and Lysholm scores increased significantly from pre- to postoperatively ( P < .001). A higher preoperative Tegner score led to a significantly lower risk for conversion to TKA ( P = .001), and a preoperative body mass index of ≥35 was associated with a significantly higher risk ( P = .019), as was female sex ( P = .046). Radiological parameters remained within physiological ranges. The postoperative joint line conversion angle did correlate with postoperative functional outcome but not with TKA conversion. Conclusion: Long-term results of HTO for medial compartment OA or cartilage defects with underlying varus deformity were good to excellent. In particular, patients who underwent HTO+ACI presented excellent long-term survival rates. HTO, therefore, delays or prevents TKA implantation, especially in young, active patients with medial compartment damage.